Promoting therapist longevity: exploring sexual offending treatment providers' experiences of workplace support. Issue 3 (2nd September 2018) - Willis, Gwenda M.; Prescott, David S.; Levenson, Jill S.
ABSTRACT: Vicarious trauma and burnout are not uncommon among therapists working with individuals who have sexually abused, which highlights the importance of workplace support. The current study aimed to explore sexual offending treatment providers' experiences of workplace support, including support from supervisors and managers, using a mixed-methods approach. Participants ( N = 189) completed an anonymous online survey. While quantitative data suggested that participants felt generally supported in their work, qualitative data highlighted nuances in participants' experiences. Support typically came from participants' colleagues and/or supervisors, although supervisory support was sometimes inadequate. Support from senior management was often lacking. Participants described their best supervisors as genuine, warm, empathic, promoting professional growth, knowledgeable and collaborative. Participants' best employers were described in similar ways, in addition to providing good contractual arrangements and effective management systems. Implications for strengthening workplace support that may buffer challenges faced by clinicians, prevent adversarial outcomes and foster therapist longevity are discussed.